Dietary adherence and health belief among malay with type 2 diabetes mellitus patients in the diabetes centre, hospital Universiti Sains Malaysia (HUSM) - Kow Fang, Fang (Universiti Sains Malaysia, 2009)
Type 2 Diabetes mellitus (DM) is now recognized as a major global health problem of pandemic proportions. Adherence to diabetes self care management regimen is important for controlling Type 2 DM. Unfortunately, low rate of dietary adherence had been found. Health belief is considered as one of the factors that influence the performance of dietary adherence. The purpose of this study was to determine the level of diabetic dietary adherence, diabetic health beliefs and their association. A quantitative study using the HBM framework was involved with 136 Malay subjects with Type 2 DM in Pusat Diabetes, HUSM, Kelantan, Malaysia. The validated Summary Diabetes SelfCare Activities (SDSCA) scale with reliability alpha 0.68 and modified Health Belief Model Diabetes Scale with reliability alpha 0.69-0.82 being used. Ethical clearance was obtained from Ethical and Research Committee of USM. Duration of data collection is approximately I month from February 2009 to March 2009. Data were analyzed via ChiSquare and Fisher's Exact test. There were 64% respondents in this study who adhered to their diabetic dietary regimen. Majority of the respondents had high positive beliefs of diabetes on susceptibility to diabetic complication and benefit which were 90% and 95% respectively. While both of the severity and barriers domain showed just 23% of respondent had high positive belief. However, this study had identified that there were certain false beliefs of diabetes especially in severity and barriers domain. Perceived susceptibility, benefits, and barriers in following diabetic dietary regimens were significantly associated with diabetic dietary adherence with the p <0.0001, p = 0.009, and p = 0.028 respectively, while perceived severity showed no significant association with dietary adherence (p = 0.843). As a conclusion, the prediction of HBM is most likely true except for the perceived severity domain. Thus, health care providers need to establish methods, techniques or guideline to change false belief of diabetes and overcome the barriers among OM patients.